The Influence of Consumer Trust, Cash On Delivery (COD) on Purchasing Decisions Through Perceived Risk on Lazada - Hermawan, Bagus; Rr. Hawik Ervina Indiworo; Ratih Hesty Utami Puspitasari (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of consumer trust and cash on delivery on purchasing decisions through perceived risk on Lazada. The study is conducted using quantitative research, employing a questionnaire as the research instrument. The sample consists of 200 respondents, selected using a non-probability sampling method, as the total population size is unknown. The research data were analyzed using the Structural Equation Modelling (SEM) statistical method with the Smart PLS 4 application. The study’s data has met validity and reliability tests, indicating that the results comply with the model requirements to proceed to hypothesis testing. The findings of this study show that: (1) Consumer trust has a positive and significant impact on perceived risk on Lazada, (2) Cash on Delivery (COD) has a positive and significant impact on perceived risk on Lazada, (3) Perceived risk does not affect purchasing decisions on Lazada, (4) Consumer trust has a positive and significant impact on purchasing decisions on Lazada, (5) Cash on Delivery (COD) has a positive and significant impact on purchasing decisions on Lazada, (6) Consumer trust has a positive and significant impact on purchasing decisions through perceived risk on Lazada, (7) Cash on Delivery (COD) has a positive and significant impact on purchasing decisions through perceived risk on Lazada.